Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$$\lim_{\Delta x\rightarrow0}\sum_{k=1}^{n-1}\int_{k+\Delta x}^{k+1-\Delta x}x^m dx$$

How to integrate the above integral?


$$\lim_{\Delta x\rightarrow0}\int_{2-\Delta x}^{2+\Delta x}x^m dx$$

Does this intergral give $\space\space\space\space$ $2^m\space\space$ as the output?


Are my following steps correct?

$\lim_{\Delta x\rightarrow0}\sum_{k=1}^{n-1}\int_{k+\Delta x}^{k+1-\Delta x}x^m dx$ =

$\lim_{\Delta x\rightarrow0}\sum_{k=1}^{n-1}\int_{k+\Delta x}^{k+1-\Delta x}x^m dx$ $+$ $\lim_{\Delta x\rightarrow0}\sum_{k=1}^{n-1}\int_{k+1-\Delta x}^{k+1+\Delta x}x^m dx$ $-$ $\lim_{\Delta x\rightarrow0}\sum_{k=1}^{n-1}\int_{k+1-\Delta x}^{k+1 +\Delta x}x^m dx$ =

$\lim_{\Delta x\rightarrow0}\int_{1+\Delta x}^{n+\Delta x}x^m dx$ $-$ $\lim_{\Delta x\rightarrow0}\sum_{k=1}^{n-1}\int_{k+1-\Delta x}^{k+1 +\Delta x}x^m dx$ =

$\lim_{\Delta x\rightarrow0}\int_{1}^{n}x^m dx$ $+$$\lim_{\Delta x\rightarrow0}\int_{n}^{n+\Delta x}x^m dx$ $-$ $\lim_{\Delta x\rightarrow0}\int_{1}^{1+\Delta x}x^m dx$ $-$

$\lim_{\Delta x\rightarrow0}\sum_{k=1}^{n-1}\int_{k+1-\Delta x}^{k+1 +\Delta x}x^m dx$ = $\lim_{\Delta x\rightarrow0}\int_{1}^{n}x^m dx$ + 0 - 0 - 0 = $\lim_{\Delta x\rightarrow0}\int_{1}^{n}x^m dx$

= $\int_{1}^{n}x^m dx$

share|cite|improve this question
This version of Edit2 looks good. – Brian M. Scott Jan 8 '13 at 21:08
up vote 3 down vote accepted

For the first question: $$ \begin{align} \lim_{\Delta x\to0}\,\left|\,\int_k^{k+1}x^m\,\mathrm{d}x-\int_{k+\Delta x}^{k+1-\Delta x}x^m\,\mathrm{d}x\,\right| &=\lim_{\Delta x\to0}\,\left|\,\int_k^{k+\Delta x}x^m\,\mathrm{d}x+\int_{k+1-\Delta x}^{k+1}x^m\,\mathrm{d}x\,\right|\\ &\le\lim_{\Delta x\to0}2\Delta x(k+1)^m\\ &=0 \end{align} $$ we get $$ \begin{align} \lim_{\Delta x\to0}\sum_{k=1}^{n-1}\int_{k+\Delta x}^{k+1-\Delta x}x^m\,\mathrm{d}x &=\sum_{k=1}^{n-1}\int_k^{k+1}x^m\,\mathrm{d}x\\ &=\int_1^nx^m\,\mathrm{d}x \end{align} $$ For the Edit:

For $\Delta x<1$, $$ \left|\,\int_{2-\Delta x}^{2+\Delta x}x^m\,\mathrm{d}x\,\right|\le2\cdot3^m\Delta x $$ Therefore, $$ \lim_{\Delta x\to0}\,\int_{2-\Delta x}^{2+\Delta x}x^m\,\mathrm{d}x=0 $$ For your steps: If you would give the justification for each step, it would help us in commenting on what is correct and what might be wrong and help you in seeing what is right.

share|cite|improve this answer
Ok, I didn't notice this answer. – Inquisitive Jan 8 '13 at 21:15


$$\sum_{k=1}^{n-1}\int_{k+\Delta x}^{k+1-\Delta x}x^m dx=\int_1^nx^mdx-\left(\int_1^{1+\Delta x}x^mdx+\sum_{k=2}^{n-1}\int_{k-\Delta x}^{k+\Delta x}x^mdx+\int_{n-\Delta x}^nx^mdx\right)$$

Let $M$ be any upper bound for $x^m$ on $[1,n]$; then

$$\begin{align*} \int_1^{1+\Delta x}x^mdx+\sum_{k=2}^{n-1}\int_{k-\Delta x}^{k+\Delta x}x^mdx+\int_{n-\Delta x}^nx^mdx&\le M\left(\Delta x+2(n-2)\Delta x+\Delta x\right)\\ &=2M\Delta x(n-1)\;. \end{align*}$$

Added: The same reasoning shows that

$$\lim_{\Delta x\rightarrow0}\int_{2-\Delta x}^{2+\Delta x}x^m dx=0\;:$$

if $M$ is any bound on $x^m$ over the interval $[1,3]$, say, the integral is bounded by $2M\Delta x$.

By the way, you really shouldn’t use $x$ both in $\Delta x$ and as the variable of integration. The new limit, for instance, ought to be

$$\lim_{\Delta x\rightarrow0}\int_{2-\Delta x}^{2+\Delta x}t^m dt$$

or the like, with similar changes in the original problem.

share|cite|improve this answer

$$\lim_{s\rightarrow0}\frac1s\int_{2-s}^{2+s}x^m\mathrm dx=2\cdot2^m$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.